2010
DOI: 10.1088/1751-8113/43/30/305002
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation of polymers modeled by generalized Husimi cacti

Abstract: We focus on the generalized Husimi cacti, which are dual structures to the dendrimers but, distinct from the latter, contain loops. We determine their complete spectra by making use of the normal mode analysis. These spectra have been used in computing some physical quantities, such as the averaged monomer displacement and the mechanical relaxation moduli with its two components: the storage and the loss modulus. We also study the dynamics of Husimi cacti in solutions, introducing the hydrodynamic interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…IV, SD; scaling behavior is, on the other hand, the rule for linear chains and for fractals. [28][29][30][31] In fact, for FD the corresponding curves in the region of intermediate frequencies can be approximated through logarithmic forms. 8 The broadening of the spectra with growing q, as discussed above, manifests itself through a broadening of the [G (ω)]-shapes.…”
Section: Discussionmentioning
confidence: 99%
“…IV, SD; scaling behavior is, on the other hand, the rule for linear chains and for fractals. [28][29][30][31] In fact, for FD the corresponding curves in the region of intermediate frequencies can be approximated through logarithmic forms. 8 The broadening of the spectra with growing q, as discussed above, manifests itself through a broadening of the [G (ω)]-shapes.…”
Section: Discussionmentioning
confidence: 99%
“…For semiflexible chains Equation 16 was derived by Bixon and Zwanzig [35] using projection operator techniques. [33,34] We note that for STP the average of d a Á d b with respect to the Boltzmann distribution expðÀV STP =k B TÞ is…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…For several classes of macromolecules the GGS method has been applied (in many cases semi-analytically) to dendrimers, [4] to mesh-like [5,6] and star-based networks, [7,8] to dendritic [9,10] and regular hyperbranched structures [11,12] and to several kinds of fractals. [13][14][15][16] However, the GGS concept neglects important aspects, such as the excluded volume and the hydrodynamic interactions, as well as the role of stiffness. It is the latter aspect on which we focus here, since stiffness is often fundamental, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the Laplacian eigenvalues for some classes of graphs have been determined exactly, including regular hypercubic lattices, 1,9 dual Sierpinski gaskets, 10,11 Vicsek fractals, 12,13 dendrimer also known as Cayley tree, 14 and Husimi cacti. 15,16 Recent empirical research indicated that some real-life networks (e.g., power grid) display small-world behavior. 17 Moreover, these networks are simultaneously characterized by an exponentially decaying degree distribution, 18 which cannot be described by the above-mentioned networks.…”
Section: Introductionmentioning
confidence: 99%